Law Enforcement and Efforts to Prevent Doping Abuse in Football Athletes - Laila Himmatul Fajriyah; Emmilia Rusdiana; Rohmatul Faizah (Universitas Negeri Surabaya, 2024)
Athletes are professional individuals trained to possess agility, strength, and speed for competitive performance. Football athletes, in particular, exhibit a high spirit of competitiveness to bring pride to their country, club, and region. This intense desire to win has led some athletes to resort to doping as a shortcut to enhance performance. This study aims to examine the legal framework governing the use of doping among football athletes in Indonesia, the enforcement of these laws, and the preventive efforts undertaken by the Bojonegoro Regency PSSI Association. Using a sociological juridical approach, data was collected through field studies and interviews with relevant stakeholders. The findings reveal that doping is strictly prohibited in football and is subject to legal sanctions, especially when involving narcotics-type substances. Law enforcement has been effectively implemented against offenders. Furthermore, the Bojonegoro PSSI Regency Association has taken active preventive measures by organizing awareness campaigns and educational sessions. These initiatives are conducted in collaboration with local hospitals and the National Narcotics Agency (BNN) of Tuban Regency. Such efforts aim to enhance athletes' understanding of the dangers and legal consequences of doping, thereby fostering a culture of fair play and clean competition in regional football.